Terrestrial dissolved organic carbon subsidizes estuarine zooplankton: An in situ mesocosm study. (11th October 2015) - Hitchcock, James N.; Mitrovic, Simon M.; Hadwen, Wade L.; Roelke, Daniel L.; Growns, Ivor O.; Rohlfs, Ann‐Marie
Abstract: Freshwater inflows play an important role in delivering dissolved organic carbon (DOC) to estuaries. Episodic inputs of DOC may support increased bacterial production. However, the role of DOC in supporting zooplankton production is widely debated. To evaluate this role we performed an in situ mesocosm experiment in the Bega River estuary, Australia. We added a DOC leachate derived from terrestrial vegetation to 400 L mesocosm bags as treatments of +1.5, +3, and +16 mg C L −1 and monitored changes in carbon, nitrogen, phosphorus, bacteria, chlorophyll a (Chl a ), and zooplankton over 22 d. Bacterial biomass peaked at day 2 and was highest in the +16 mg C L −1 treatment. Chl a was not significantly different between treatments. Mesozooplankton was dominated by copepodites of Gladioferens pectinatus and Sulcanus conflictus between days 5–9 and by adults between days 9–15. Significantly higher numbers of copepods were present in the +16 treatment followed by the +3 mg C L −1 treatment compared with the controls. Stable carbon isotope signatures of copepods in the +16 mg C L −1 treatment were significantly different from the control and showed leachate carbon supported between 29.3% and 55.8% of copepod biomass. These results suggest that the impact of allochthonous DOC loading events on estuarine zooplankton occurs over short periods, and that the magnitude of response is, in part, controlled by the quantity of bioavailable DOC loaded to the system. Our findings underscore the importance of microbial dynamics stimulated by DOC loading events from freshwater inflows as a trophic path in estuarine food webs.